Differential Characteristics and Outcomes of Urgent/Emergent Versus Elective Aortic Valve Replacement - Joseph E. Ebinger; Aakriti Gupta; Tzu Yu Huang; Marcella A. Kelley; Christin Thompson; Maria Platanis; Susan Cheng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Despite the slowly progressive nature of aortic stenosis, a proportion of aortic valve replacements (AVRs) still occur on an urgent/emergent basis. We sought to characterize the predictors, outcomes, and potential opportunities to prevent urgent/emergent AVRs. Methods We analyzed Medicare data to identify patients undergoing AVRs from 2017 to 2022. We used multivariable regression to identify factors associated with nonelective AVRs; we also examined the association of nonelective AVRs with clinical outcomes and health care costs. Results In total, 15 305 patients (16% urgent/emergent) underwent AVR during the study period. Compared with patients undergoing elective AVRs, those receiving urgent/emergent AVRs were more frequently of Black race or Hispanic ethnicity, and less likely to have received a diagnosis of aortic stenosis, despite 91.7% having seen a cardiologist or primary care provider in the prior year. In multivariable‐adjusted analyses, dual Medicare–Medicaid enrollment, male sex, and recent heart failure hospitalization were associated with increased risk for urgent/emergent AVR; conversely, recent aortic stenosis diagnosis and cardiologist visit were associated with lower odds of urgent/emergent AVR. In turn, urgent/emergent compared with elective AVR increased risk for in‐hospital death, intensive care unit admission, and discharge to a facility versus home, in addition to longer lengths of stay and higher health care costs. Conclusions Urgent/emergent AVR occurs more frequently among Black, Hispanic, and dual Medicare–Medicaid‐eligible patients. Nonelective AVR is also associated with worse hospital outcomes as well as greater health care costs. Importantly, variable timing in diagnosis of aortic stenosis appears to be a key determinant; thus, augmented screening efforts may improve outcomes and reduce disparities.